Brackish Water Desalination Using Moringa Oleifera Seed Powder, Coconut Shell Activated Charcoal And Vetiver Grass : A Review - Mr. K. Srinivasan; Barathan. R; Dhiliban. P; Dinagar. R; Senghathirselvan. M (International Journal of Scientific Research in Civil Engineering, 2022)
Desalination of water is generally expensive, requires more energy and specialized equipment. This work is to present an overview of desalination of brackish water by developing filter model using naturally available materials to produce fresh water for supplementing water supplies to the common people in smaller quantity. The bio filter model is constructed with Moringa oleifera seed powder, coconut shell activated charcoal and Chrysopogan zizanioides (vetiver grass – dried form) coupled with traditional sand filter. Moringa oleifera seeds are good in coagulation whereas activated charcoal prepared from coconut shell is a good adsorbent and these three materials are capable of reducing the amount of salts, pollutants present in water. This technique is a small-scale scheme and easily employed for intermittent use. As the filter is made from renewable materials found in abundance it provides a solution to environmental problems and offer an additional value to the agricultural economy. The potential of the materials used is determined by analyzing physical and chemical characteristics like pH, Conductivity, Turbidity, TDS, Hardness, Chloride, Sulphate, Nitrate, Fluoride, DO, BOD, COD and E. coli as per Indian Standards. The bio filter model improves the quality of water suggesting that the application of this bio filter containing natural products is effective to treat the polluted water in an economic and eco- friendly manner. This water treatment technology may offer a practical, cheap, appropriate and sustainable solution for producing potable water in some developing nations.
Keywords: Desalination; Brackish Water; Coagulant; Adsorbent; Activated Charcoal; Energy Efficient